2015
DOI: 10.1017/s1755773914000435
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the limits: involvement in illegal political activities

Abstract: The purpose of this study is to examine the adolescents who cross the boundaries of legality, also including illegal political means in their political action repertoire. The data comprised of questionnaire responses from middle and late adolescents in a Swedish city of around 130,000 citizens. Analyses of covariance, EXACON, and logistic regression were used to examine the extent to which adolescents including illegal political activities in their political activity repertoire compare with their legally orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Kuhn's (2004) study showed that German adolescents spending less time with parents were more willing to use violent political action, and Schmid's study (2012) revealed that parents and peers influenced social responsibility and in turn, also illegal or violent actions of 16‐year‐old Germans. With regard to the school environment, data from Sweden showed that adolescents who perceived their teachers as unfair were more likely to be involved in illegal political activities (Dahl & Stattin, 2016).…”
Section: The Role Of Problematic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuhn's (2004) study showed that German adolescents spending less time with parents were more willing to use violent political action, and Schmid's study (2012) revealed that parents and peers influenced social responsibility and in turn, also illegal or violent actions of 16‐year‐old Germans. With regard to the school environment, data from Sweden showed that adolescents who perceived their teachers as unfair were more likely to be involved in illegal political activities (Dahl & Stattin, 2016).…”
Section: The Role Of Problematic Developmentmentioning
confidence: 99%
“…Nevertheless, it should be acknowledged that problematic individual development could be influential in an indirect way. Adolescents' negative attitudes towards authority or their perceptions of parental over‐controlling and undemocratic behavior might be associated with a greater readiness for non‐normative participation (Dahl & Stattin, 2016; Glatz & Dahl, 2016), but it is possible that this effect does not occur unless socialization experiences translate into institutional distrust. Our additional analyses suggested the possibility that poor relationships with teachers contributed to a lower institutional trust, which, in turn, led to a greater readiness for non‐normative participation.…”
Section: The Role Of Problematic Developmentmentioning
confidence: 99%
“…We argue that boycotting or joining a strike are different from peacefully demonstrating because they involve more costly, potentially illegal, and occasionally violent actions (Dahl and Stattin 2014;Dalton 2008;Wolfsfeld et al 1994). This form of engagement requires more effort and coordination than peaceful demonstration and is rarely used to engage in electoral politics.…”
Section: Do Government Positions Held By Women Matter?mentioning
confidence: 90%
“…While this research suggests that protest, and specifically illegal protest, is an incremental and cumulative political behavior, most of the literature that surveys individual predictors of illegal protest fails to control for prior protest participation. Among the very scarce studies that aim at understanding the individual antecedents of specifically illegal protest, most works just run different cross-sectional regressions for legal and illegal protest and compare the results, as if participants in those groups were different sets of people (see, for example, Dahl & Stattin, 2014; and Finkel et al, 1989). However, a study that surveyed legal and illegal protest in 17 Western democracies found that on average, 87.5% of illegal protestors had also engaged in legal protest, and for the US that percentage was 100% (Roller & Weßels, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%